Selective Changes of GABAA Channel Subunit mRNAs in the Hippocampus and Orbitofrontal Cortex but not in Prefrontal Cortex of Human Alcoholics - Jin, Zhe; Bazov, Igor; Kononenko, Olga; Korpi, Esa R.; Bakalkin, Georgy; Birnir, Bryndis (Frontiers in Cellular Neuroscience, 2012)
Alcohol dependence is a common chronic relapsing disorder. The development of alcohol dependence has been associated with changes in brain GABA-A channel-mediated neurotransmission and plasticity. We have examined mRNA expression of the GABA-A channel subunit genes in three brain regions in individuals with or without alcohol dependence using quantitative real-time RT-PCR assay. The levels of selective GABA-A channel subunit mRNAs were altered in specific brain regions in alcoholic subjects. Significant increase in the α1, α4, α5, β1 and γ1 subunit mRNAs in the hippocampal dentate gyrus region, and decrease in the β2 and δ subunit mRNAs in the orbitofrontal cortex were identified whereas no changes in the dorsolateral prefrontal cortex were detected. The data increase our understanding of the role of GABA-A channels in the development of alcohol dependence.